𝜸′ Precipitation and Growth Kinetics in Mechanically Alloyed Ni–Al - QingXin Tang; Shigeharu Ukai; Akinobu Minami; Shigenari Hayashi (Advances in Materials Science and Engineering)
The precipitation and growth kinetics of γ′ precipitates, which are strengthening factors in Ni-base oxide dispersion strengthened (ODS) superalloys, were investigated. The cuboidal-type γ′ precipitates are formed in conventional arc-melted Ni–Al alloys, whereas spherical-type precipitates are formed in the mechanically alloyed (MAed) specimens. The morphology is controlled by a lattice misfit between the γ′ precipitates and the matrix at the aging temperature of 800°C. The growth kinetics of the γ′ precipitates can be followed by Ostwald ripening. The Arrhenius plot yielded a lower activation energy for the solute atom diffusion in MAed specimens, which is attributed to their high dislocation density and nanosized grains.